Sosiolinguistics Alih Kode dan Campur Kode dalam Ceramah Habib Umar Al-Muthohhar - Irrohman, Arju Taufiq; Rokhman, Fathur (Jurusan Bahasa dan Sastra Indonesia Universitas Negeri Semarang, 2021)
Lecture is a way of conveying ideas or messages to others. In religious lectures conducted by Habib Umar Al-Muthohhar, it is often found that in lecturing he used the code of switching and mixing. The objectives of this study are (1) to describe the type of code-switching in Habib Umar Al-Muthohhar's lectures, (2) to describe the type of code-mixing in Habib Umar Al-Muthohhar's lectures (3) to describe the factors that caused the code-switching in Habib Umar Al-Muthohhar's lectures, (4) describe the factors that caused the code-mixing in Habib Umar Al-Muthohhar's lectures. The theoretical approach that used in this research is sociolinguistics. The data of this study were utterances spoken by Habib Umar Al-Muthohhar in some lectures that allegedly contained the symptoms of code-switching and code-mixing. The data collection method in this study is using the listening method with the speech free listening technique. The results showed that there were several types of code-switching and code-mixing used by Habib Umar in his lectures. The types of code-switching found were internal, external, metaphorical, situational, temporary, and permanent. The type of code-mixing in Habib Umar Al-Muthohhar's lecture mixed the code in and out. The form of code-mixing is the insertion of words, repetitions, phrases, and clauses. Factors that caused the code-switching are speakers, speech partners, subject matter, and evokes a sense of humor. The factors that caused the code-mixing are role identification, variety identification, desire to explain or explain, and show familiarity.